High-performance non-enzymatic biofuel cells based on an organic copper complex cathode and a nanoporous gold nanoparticle anode. Issue 13 (17th December 2018) - Zhao, Shifan; Gai, Panpan; Yu, Wen; Li, Haiyin; Li, Feng
Abstract : We developed non-enzymatic biofuel cells based on organic copper complex and nanoporous gold nanoparticle electrocatalysts in a neutral medium. Abstract : We developed efficient compartment-less non-enzymatic biofuel cells (NEFCs) with an electrografted copper complex of 3, 5-diamino-1, 2, 4-triazole and nanoporous gold nanoparticles as catalysts, which could not only work in a neutral solution, but also drive the self-powered sensing of pyrophosphate via the stronger coordination of Cu 2+ with O than N at the cathode.